Development of curriculum design evaluation instruments in strengthening Al-Irsyad ideology in Indonesia - Joko Subando; Badrun Kartowagiran; Sudji Munadi (International Journal of Evaluation and Research in Education (IJERE), 2021)
The purpose of this research was to develop a curriculum design evaluation instrument in strengthening Al-Irsyad ideology. The research activity began with a literature review on the curriculum then continues with the development of the instrument. The results of the development of the instrument items were validated by 11 experts and tested on a limited scale by involving 17 teachers from Al-Irsyad Junior High School, Surakarta, Cirebon, and Purwokerto, Indonesia. The next activity was an expanded trial involving 53 teachers from Al-Irsyad schools in West Java, Central Java, and East Java, the territory of the Republic of Indonesia. Data from expert reviews were analyzed by using Aiken's formula. Limited trial data were analyzed with the EFA model using the help of the SPSS program, and data from the extended trial results were analyzed by CFA using the help of the Smart PLS version 2.0 program. The results indicated that the instrument has a good validity guarantee because the loading factor value ranges from 0.5571-0.9463 (>0.5), and the AVE value ranges from 0.5901-0.8051 (>0.5), and has guaranteed reliability because of the CR value ranges from 0.8394-0.9397 (>0.7) and Cronbach alpha ranges from 0.7692-0.9286 (>0.7). The instrument feasible to be used as a measurement tool in evaluating the Al-Irsyad curriculum design in Indonesia.